Recreational and sports nature usage in Lviv region: origins and geospatial analysis - Nazaruk, M. M.; Khudoba, V. V. (Man and Environment. Issues of Neoecology, 2022)
In the process of recreation, nature acts as one of the leading factors of rest and recovery, restoration of physical and neuropsychological strength of a person. Recreational and sports nature usage is implemented through a complex of activities related to the usage of natural resources for the purpose of improving people’s health, restoring their physical and psychological well-being, and expanding the ecological and cultural outlook. The study of geospatial features of recreational and sports resources contributes to their use and perspective of their consumption. Purpose. To study the retrospective principles of formation, historical and natural prerequisites for development and geospatial analysis of the recreational organization of sports and nature usage in Lviv region, as well as prospects for further their development. Results. In general, the climatic conditions within Lviv region are equally suitable for recreational and sports usage. Favorable conditions for seasonal recreation types in the region are approximately 10 months within the year. The mountainous realm of the region is the major region for the winter sports and recreation. Mountain skiing recreational and sports nature usage is developing in 10 of the 73 united territorial communities of the region. Lviv region has a good supply of water resources for recreational and sports nature usage. Water bodies within the Dniester basin are the most involved in recreational activities. They are used for rafting, diving, swimming, fishing. Less developed reservoirs within the basin of the Western Bug River, which are involved in swimming, rafting and fishing. An important direction of sports recreation is air space usage, such as paragliding, ballooning, parachuting, and flying on light aircraft. Conclusions. Irrational and non-professional lands usage for health and recreational purposes do not always contribute to the development of recreational and sports nature usage within the territorial communities of the Lviv region. It is expedient to ensure the introduction of market regulators into the practice of recreational and sports nature usage; the development of methods of recreational ecosystem services assessment and the implementation of monitoring of the state and use of recreational and sports resources.